TikTok Addiction and Academic Procrastination Among College and University Students in Pakistan (Journal of Asian Development Studies, 2025)
TikTok is a social media app that features short-form videos ranging from a few seconds to several minutes. For gratification purposes, college and university students have increasingly engaged in watching these videos. According to existing studies, excessive use of this app leads to academic procrastination; however, such studies are scarce in the Pakistani context. Therefore, the objective of this study was to explore the impact of TikTok addiction on academic procrastination among Pakistani college and university students (N = 222), aged 15 to 35, who had been using TikTok for at least one year. A purposive sampling technique and a cross-sectional correlational design were employed. The findings indicated a significant and positive effect of TikTok addiction on academic procrastination, accounting for 9% of the variance. Implications are discussed for student welfare at the end of study.